On the parametic interest of the Black-Scholes equation - Amnuay Kananthai (2018)
We have discovered some parametics λ in the Black-Scholes equation which depend on the interest rate r and the Volatility σ and later is named the parametic interest. On studying the parametic interest λ, we found that such λ gives the sufficient condition for the existence of solutions of the Black-Scholes equation which is either weak or strong solutions. © 2013 by the Mathematical Association of Thailand. All rights reserved.